Decreased Serum Levels of Sphingomyelins and Ceramides in Sickle Cell Disease Patients - Aslan, Mutay; Kıraç, Ebru; Kaya, Sabriye; Özcan, Filiz; Salim, Ozan; Küpesiz, Osman Alphan (Lipids, 2018)
Limited data are available on the serum levels of different sphingomyelin (CerPCho) and ceramide (CER) species in sickle‐cell disease (SCD). This study was aimed at identifying the levels of C16–C24 CerPCho and C16–C24 CER in serum obtained from SCD patients and controls. Circulating levels of neutral sphingomyelinase (N‐SMase) activity, ceramide‐1‐phosphate (C1P), and sphingosine‐1‐phosphate (S1P) were also determined. Blood was collected from 35 hemoglobin (Hb)A volunteers and 45 homozygous HbSS patients. Serum levels of C16–C24 CerPCho and C16–C24 CER were determined by an optimized multiple reaction monitoring (MRM) method using ultrafast liquid chromatography (UFLC) coupled with tandem mass spectrometry (MS/MS). Serum activity of N‐SMase was assayed by standard kit methods, and C1P and S1P levels were determined by enzyme‐linked immunosorbent assay. A significant decrease was observed in the serum levels of C18–C24 CerPCho in patients with SCD compared to controls. No significant difference was found in C16 CerPCho levels between the two groups. Very‐long‐chain C22–C24 CER were significantly decreased in SCD, while long‐chain C16–C20 CER levels showed no significant difference between SCD patients and controls. Significant positive correlation was found between the serum total cholesterol levels and C18–C24 CerPCho and C22–C24 CER in SCD patients. Patients with SCD had significantly elevated serum activity of N‐SMase as well as increased circulating levels of C1P and S1P compared to controls. The decrease in serum levels of C18–C24 CerPCho in patients with SCD was accompanied by decreased levels of C22–C24 CER. Future studies are needed to understand the role of decreased CerPCho and CER in the pathophysiology of SCD.